Leisure, sport and tourism, politics policy and planning - Veal, Anthony James (CABI tourism texts, 2017)
A comprehensive, multidisciplinary approach to public policymaking and planning in the leisure, sport and tourism sectors, this book: - examines the theoretical issues underpinning public sector policymaking such as political ideologies, leisure wants, needs, demand and benefits, and human rights in leisure, sport, tourism and culture; - discusses the debates surrounding the role of the state versus market, and models of organizational decision-making; and - uses applied sections addressing strategic planning and performance evaluation to provide a link between theory and practical analytical techniques. As well as extensive updating of sources, this new edition examines such topics as libertarianism, theocracy, anti-establishment politics, and the concept of generations. A new chapter presents discussions of a number of 'issues and challenges' facing the leisure, sport and tourism sector. Introducing the subject for undergraduate and postgraduate students of leisure, sport and tourism, this book is also a useful addition to the shelf of any policy maker or practitioner within the industries.